The impact of demographics on health and health care race, ethnicity and other social factors - Kronenfeld, Jennie J. (Bingley, U.K. : Emerald, 2010)
Volume 28, The Impact of Demographics on Health and Healthcare: Race, Ethnicity and other Social Factors, focuses on differences in health and health care as linked to important social factors. The first section, Social Factors Leading to Differences in Health and Health Care, reviews basic material on the topic. The second section on Racial and Ethnic Factors in Differences in Health and Health Care is the largest section of the book, and includes 6 articles looking at racial disparities on a variety of topics such as knowledge of hepatitis C Virus, health services received and patients experiences in seeking health care, use of CAM (complementary and alternative medicine) services, and the role of social capital in class and race health disparities in health information seeking behaviour. The third section includes three articles focused on geographic and community factors. The fourth section has two articles on gender and age and gender and language. The fifth section has two articles on lifecourse issues such as maternal depression and hospice care.
Social factors leading to differences in health and health care : the influence of factors such as race/ethnicity, geography, and gender / Jennie Jacobs Kronenfeld -- Racial disparities in knowledge of hepatitis C virus (HCV) / Alicia Suarez -- Medicare and racial disparities in health : fee-for-service v. managed care / Noah J. Webster -- How much time do Americans spend seeking health care? : racial and ethnic differences in patient experiences / Deborah Carr, Yoku Ibuka, and Louise Russell -- Can the behavioral model explain immigrant status and ethnic differences in U.S. adults CAM use? / Georgiana Bostean -- Class and race health disparities and health information seeking behaviors / Cirila Estela Vasquez Guzman, Gilbert Mireles, Neal Christopherson, and Michelle Janning -- Racial disparities in stillbirths / Vicki Dryfhout -- Habilitative therapy among preschool children : regional disparities in the early intervention population / Richard Lee Rogers -- Consumer-directed health insurance vs. managed care : analysis of health care utilization and expenditures incurred by employees in a rural area / Cecilia M. Watkin, John White, David F. Duncan, David K. Wyant, Thomas Nicholson, Jagdish Khubchandani and Lakshminarayana Chekuri -- Some considerations regarding gender when a health care interpreter is helping providers and their limited English proficient patients / Stergios Roussos, Mary-Rose Mueller, Linda Hill, Nadia Salas, Melbourne Hovell and Veronica Villarreal -- Hidden gender inequalities in old age : equal treatment does not mean equal results / Sally Bould -- Mothers perspectives on enhancing consumer engagement in behavioral health treatment for maternal depression / Sandraluz Lara-Cinisomo, Ellen Burke Beckjord, and Donna Keyser -- Mediating hospice care : mapping relations of ruling in the interdisciplinary group meeting / Maria DiTullio and Douglas MacDonald.
Print version record
Keywords: Health & Fitness -- Health Care Issues; Social Science -- Sociology -- General; Medical -- Health Care Delivery; Health systems & services; Sociology; Health services accessibility -- Case studies; Discrimination in medical care -- Case studies; Minorities -- Medical care -- Case studies